2012
DOI: 10.1016/j.clnu.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipid droplet size on satiety and peptide secretion is intestinal site-specific

Abstract: Compared to larger fat droplets, smaller droplets significantly affect satiety, gastric emptying and gut peptide release, but with the effect being dependent on the intestinal location of fat delivery. DUTCH TRIALREGISTER: NTR1515.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…Similar to other studies, the smaller fat droplet size and slower gastric emptying of LE1 than LE2 resulted in increased fullness and decreased hunger sensations (40,43,44). The faster gastric emptying, reduced intestinal secretion, and lower fat digestibility of LE3 resulted in the highest and lowest ratings of hunger and fullness sensations, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to other studies, the smaller fat droplet size and slower gastric emptying of LE1 than LE2 resulted in increased fullness and decreased hunger sensations (40,43,44). The faster gastric emptying, reduced intestinal secretion, and lower fat digestibility of LE3 resulted in the highest and lowest ratings of hunger and fullness sensations, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…However, in a study comparing liquid and semi-solid meals, the latter was more satiating, even though there was no difference in CCK-8 or GLP-1 secretion (36). It has also been shown that the detection of fat in the duodenum can significantly reduce hunger, increase fullness, and delay gastric emptying (20).…”
Section: Discussionmentioning
confidence: 97%
“…7 An in vitro model has suggested a plasma level as high as 2.5 g litre 21 to optimise coagulation altered by a dilution coagulopathy. 8 At term, parturients already exhibits a higher level of fibrinogen compared with non-pregnant women. 9 During PPH, a fibrinogen level ,2 g litre 21 has been shown to predict progression to more severe bleeding or the need for a haemostatic intervention, 10 although even higher levels have been suggested.…”
Section: Author's Contributionmentioning
confidence: 99%
“…For example, when a lipid emulsion is infused directly into the duodenum, gastric motility decreases and appetite is suppressed. 8 Filling the intestine with food or drink triggers a neurohumoral response mediated by the vagus nerve, the myenteric plexus, and the release of small bowel peptide hormones (e.g. CCK, glucagon-like peptide-1), which affect gastrointestinal function and slow gastric emptying.…”
mentioning
confidence: 99%
See 1 more Smart Citation